2018
DOI: 10.1124/jpet.118.251413
|View full text |Cite|
|
Sign up to set email alerts
|

Towards Further Verification of Physiologically-Based Kidney Models: Predictability of the Effects of Urine-Flow and Urine-pH on Renal Clearance

Abstract: In vitro-in vivo extrapolation (IVIVE) of renal excretory clearance (CL R ) using the physiologically based kidney models can provide mechanistic insight into the interplay of multiple processes occurring in the renal tubule; however, the ability of these models to capture quantitatively the impact of perturbed conditions (e.g., urine flow, urine pH changes) on CL R has not been fully evaluated. In this work, we aimed to assess the predictability of the effect of urine flow and urine pH on CL R and tubular dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 78 publications
6
28
0
Order By: Relevance
“…Conversely, our model accurately recapitulated the renal excretion of methamphetamine and amphetamine under acidic (urine pH = 5.0), uncontrolled (urine pH = 6.5), and alkaline (urine pH = 8.0) urine conditions ( Figure 6), and was previously shown to capture the varying renal clearance of salicylic acid and memantine as a function of urine pH (Huang and Isoherranen, 2018). We confirmed the importance of the stepwise gradient via an in-house head-to-head comparison of the urinary methamphetamine excretion using our stepwise pH gradients and the previously published (Matsuzaki et al, 2019) constant pH value. The constant pH value approach failed to recapitulate the observed data under uncontrolled (AAFE = 2.2 or 6.5) and alkaline urine condition (AAFE = 13.6) ( Supplementary Figure 5) while the stepwise pH gradient approach successfully (AAFE < 2) simulated methamphetamine urinary excretion ( Supplementary Figure 4).…”
Section: Downloaded Fromsupporting
confidence: 81%
See 2 more Smart Citations
“…Conversely, our model accurately recapitulated the renal excretion of methamphetamine and amphetamine under acidic (urine pH = 5.0), uncontrolled (urine pH = 6.5), and alkaline (urine pH = 8.0) urine conditions ( Figure 6), and was previously shown to capture the varying renal clearance of salicylic acid and memantine as a function of urine pH (Huang and Isoherranen, 2018). We confirmed the importance of the stepwise gradient via an in-house head-to-head comparison of the urinary methamphetamine excretion using our stepwise pH gradients and the previously published (Matsuzaki et al, 2019) constant pH value. The constant pH value approach failed to recapitulate the observed data under uncontrolled (AAFE = 2.2 or 6.5) and alkaline urine condition (AAFE = 13.6) ( Supplementary Figure 5) while the stepwise pH gradient approach successfully (AAFE < 2) simulated methamphetamine urinary excretion ( Supplementary Figure 4).…”
Section: Downloaded Fromsupporting
confidence: 81%
“…This better performance could be due to our strategy to use a stepwise gradient for renal tubular filtrate pH to account for the naturally continuous acidification process of tubular filtrate, although other differences such as microvilli consideration and a larger number (11 vs 7) of tubular compartments in our model may also contribute to our better performance. Further, the previous study (Matsuzaki et al, 2019) showed a relatively insensitive response of simulated renal clearance to urine pH changes. For example, their simulated amphetamine renal clearance did not change with urine pH between 5 and 8, which is inconsistent with the observed dramatic changes (Beckett and Rowland, 1965a;Beckett et al, 1969).…”
Section: Downloaded Frommentioning
confidence: 83%
See 1 more Smart Citation
“…This trend was evident also in the static Nakada model, which required a fraction re‐absorbed of 34% to recover creatinine‐trimethoprim interaction data; value that was much higher than < 10% predicted by available mechanistic re‐absorption models 40 . So far, limited evidence supports possibility of saturable tubular reabsorption of creatinine, 41 whereas reports of urine flow dependent CL R or creatinine‐to‐inulin clearance ratio have inconsistent findings 42–44 . One potential candidate for creatinine tubular re‐absorption is OAT4 expressed on the apical membrane of the proximal tubule, 45 although relevant in vitro data to support this are equivocal 10,15 .…”
Section: Discussionmentioning
confidence: 94%
“…3-6. 27 Membrane permeability (P mem ; cm/second × 10 −6 ) was calculated from the P app after assuming resistance across the cell is sum of resistances across each membrane and that apical and basolateral membranes had equal permeability. P mem and…”
Section: Initial Parameter Verification Using One-compartment Turnovementioning
confidence: 99%